2015
DOI: 10.1016/j.jneuroim.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid CXCL13 in clinically isolated syndrome patients: Association with oligoclonal IgM bands and prediction of Multiple Sclerosis diagnosis

Abstract: Cerebrospinal fluid (CSF) CXCL13 was shown to correlate with markers of intrathecal inflammation and CSF oligoclonal IgM bands (IgMOB) have been associated with a more severe Multiple Sclerosis (MS) course. We correlated CSF CXCL13 levels with clinical, MRI and CSF parameters, including CSF IgMOB, in 110 Clinically Isolated Syndrome (CIS) patients. CSF CXCL13 levels correlated with CSF cell count, total protein, IgG Index and with the presence of CSF IgGOB and IgMOB. CSF CXCL13 levels ≥15.4 pg/ml showed a good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…It has been previously demonstrated that there is an association between individual CSF molecules, such as IgM index, kappa light chains, chemokine CXCL13, neurofilament protein light chain, and glial fibrillary acidic protein with the severity of the disease evolution. 22,23 However, most of the previous studies examined one or a few molecules in correlation with limited clinical or imaging parameters, and whether a complex CSF inflammatory profile associates with disease activity has not been addressed. 22,23 With the large number of currently available DMTs, characterized by different efficacy and safety profiles, efforts are being made to implement a personalized therapeutic approach early in the disease course, which can maximize the chances of achieving disease control in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously demonstrated that there is an association between individual CSF molecules, such as IgM index, kappa light chains, chemokine CXCL13, neurofilament protein light chain, and glial fibrillary acidic protein with the severity of the disease evolution. 22,23 However, most of the previous studies examined one or a few molecules in correlation with limited clinical or imaging parameters, and whether a complex CSF inflammatory profile associates with disease activity has not been addressed. 22,23 With the large number of currently available DMTs, characterized by different efficacy and safety profiles, efforts are being made to implement a personalized therapeutic approach early in the disease course, which can maximize the chances of achieving disease control in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 However, most of the previous studies examined one or a few molecules in correlation with limited clinical or imaging parameters, and whether a complex CSF inflammatory profile associates with disease activity has not been addressed. 22,23 With the large number of currently available DMTs, characterized by different efficacy and safety profiles, efforts are being made to implement a personalized therapeutic approach early in the disease course, which can maximize the chances of achieving disease control in the long term. However, early clinical and radiological features have limited prognostic value and optimizing the treatment selection, based on the patient's expected clinical outcome, remains a significant challenge.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL13 is increased in the CSF of patients with several MS forms and its levels seem to correlate with disease activity. 15,16 …”
Section: Cerebrospinal Fluid Biomarkers Of Disease Activitymentioning
confidence: 99%
“…The B-cell chemoattractant chemokine CXCL13 was also shown to serve as a prognostic marker for conversion to CDMS in patients with CIS, especially when combined with the Barkhof MRI criteria (Festa et al, 2009;Alvarez et al, 2013;Ferraro et al, 2015;Khademi et al, 2011).…”
Section: Additional Immunological Biomarkersmentioning
confidence: 99%